TINJAUAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TERHADAP PENELANTARAN RUMAH TANGGA OLEH SUAMI SEBAGAI BENTUK KEKERASAN DALAM RUMAH TANGGA - Rosita Ibrahim Rosita; Muhammad Zainuri; Ahmad Nurwahid (P3M dan Jurusan Syariah dan Ekonomi Bisnis Islam STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
All forms of violence, especially domestic violence, are violations of human rights and crimes against human dignity as well as forms of discrimination that must be abolished, violence is not only in the form of physical violence but neglect is also a form of violence as regulated in Article 5 Letter e Law No. 23 of 2004 on PKDRT. which the act of neglect can have a negative impact on people who are victims of neglect. That the problem in this research is what are the forms of actions that are categorized as criminal acts of neglect of the household by the husband and how the sanctions are reviewed from Law No. 23 of 2004 concerning PKDRT. The method that the researcher uses is the normative research method, the data is obtained through statutory procedures, the analysis of this research is carried out by criticizing, supporting, or commenting, then making a conclusion on the research results.Based on the results of the study, the forms of household neglect are forbidding the victim to work but neglecting, not providing a living, not giving love, not providing care to the family, and not providing education to children. And the sanctions applied according to the provisions of Law Number 23 of 2004 concerning Domestic Violence regarding the criminal act of neglect of the household are regulated in Article 49 which states that